Kakovost državnega ortofota v različnih letnikih njegove izdelave ( = Quality of the national orthophoto in different years of its production) - Mojca Kosmatin Fras; Niko Fabiani; Mihaela Triglav Čekada (Geodetski Vestnik, 2014)
The results of our research are presented in which we tested the hypothesis that the quality (especially positional accuracy and semantic quality) of national orthophoto of the same territory in different time periods has being improved as a consequence of more quality input data. A review of orthophoto production and the methods of quality assessment in the observed time frame (1994-2012) are presented. Four orthophoto map sheets have been selected for the analysis, that were produced in 4 to 6 different years and where we can find also high relief. A great number of check points (between 29 in 42) has been selected in each orthophoto map sheet, which were measured in the field and orthophoto. For each map sheet and the year we calculated a root mean square error (RMSE) from discrepancies between the field and orthophoto coordinates, we also produced tables and graphs. Numerical and graphical analyses of the results clearly show the trend of decreasing RMSE value from the older to the newer orthophoto issues, thus we can confirm our hypothesis. Planimetric accuracy, assessed with the RMSE value, has been significantly improved in the observed period (roughly from 1.4 m to 0.4 m), which proves a positive impact of technological and other changes on the national orthophoto quality.